Unveiling The Silent Giant-A Case Report on Placental Chorioangioma - L, Kalpana; E, Shanthi; Christable, Evangeline (Journal of Neonatal Surgery, 2025)
Placental chorioangioma, a rare benign vascular tumor of the placenta, is the most common nontrophoblastic placental tumor. While small lesions are usually asymptomatic, larger lesions (≥4 cm) are associated with significant maternal and fetal complications, including polyhydramnios, fetal anemia, and hydrops fetalis. This case report details a 24-year-old second gravida who presented at 32 weeks of gestation with a 4.8 × 3.2 cm hyperechoic placental lesion identified on ultrasound, suggestive of chorioangioma, accompanied by polyhydramnios (AFI 22 cm). MRI confirmed the diagnosis, revealing a 5.5 × 4.4 cm intraplacental lesion near the fetal surface without myometrial invasion. The patient remained asymptomatic and was managed conservatively with regular follow-up and fetal surveillance. Steroid cover was administered at 32 weeks to promote fetal lung maturity. At 38 weeks, an elective cesarean section was performed, resulting in the delivery of a healthy 2.85 kg female neonate. Placental examination revealed a 5 × 4 cm mass on the fetal surface, confirmed histopathologically as a benign vascular neoplasm composed of capillary-sized blood vessels. Both mother and neonate had uneventful recoveries. This case highlights the importance of advanced imaging, vigilant antenatal monitoring, and multidisciplinary care in achieving favorable outcomes in pregnancies complicated by placental chorioangiomas.